Can long-term content analysis of print media be used to examine species composition, population demography and changes in distributional range of recreational fishery species?. Issue 3 (7th October 2019) - Potts, WM; Jordan, T; Childs, A-R
Abstract : Although marine recreational fisheries are socially and economically important, there is often limited funding for their monitoring and assessment. With South African anglers reporting catch declines for almost all targeted species and little long-term monitoring data available, novel methods need to be explored to provide managers with additional information. This study aimed to evaluate the efficacy of content analysis of print-media records for detecting long-term trends in species composition, size composition and distribution of selected recreational fishery species. Information for eight fishes captured in the marine shore-based fishery was collected from South Africa's most popular recreational fishery magazine, between 1960 and 2009. During the five decades, there were shifts in the catch composition, from being dominated by slow-growing, large predators to faster-growing, large predators and lower-trophic-level species. There were no significant trends in the mean and maximum sizes of the dominant species, except for dusky kob Argyrosomus japonicus, which increased significantly in the maximum size reported during the study period. The distributional range of A. japonicus and leervis Lichia amia significantly increased, and that of galjoen Dichistius capensis significantly decreased. However, it was uncertain whether these trends could be attributed to population changes, changes in angler technology and/or behaviour, or climate signals. Overall, this type of content analysis may provide a cost-effective method to examine changes in species composition and fish distributions over time, but, without detailed knowledge of shifts in angler behavioural patterns, it may not be as useful for understanding changes in the population dynamics of recreational fishery species. It is suggested that fishery-independent monitoring programmes are most suited for this type of complex fishery.